The Impact of Open Pit Mine on Nearby Watercourse Mala Rijeka, Vareš - Merzić, Azra (Bulletin of Chemists and Technologists of Bosnia and Herzegovina, 2022)
Veovača open pit mine, located near Vareš, was used for extraction of ore rich with zinc, lead, and barite from 1982 until 1988, with the floatation processing plant in the near vicinity. Water quality of Mala Rijeka, watercourse passing by the mine and the processing plant, was examined in 2019. This paper analyses the presence of selected heavy metals (Cd, Zn, Fe, Mn, Pb), sulphate anion, and electrical conductivity along the entire length of Mala Rijeka, to determine the nature of impact that the mine and the processing plant have on the watercourse. FAAS/ETAAS techniques were used to determine concentration of the heavy metals in water samples. Concentration of sulphates was determined by gravimetric (with BaSO4) method. Concentrations of Cd (